Web-Based E-Catalog Application for Kenongo Batik SMEs Tulangan Sidoarjo: Aplikasi E-Katalog Pada UKM Batik Kenongo Tulangan Sidoarjo Berbasis Web - Samtidar; M. Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2021)
Sidoarjo is one area that deserves to be put forward. The culture of batik and textile creation is interesting to explore further. With current technological developments, making data, information and matters related to information systems is very fast to be obtained and distributed to various layers of society, various circles, and various social layers. The purpose of this study was to find out how to design and build a website-based e-catalog as a medium of information for Batik Sari Kenongo. The research method used by the author in designing a website-based e-catalog as a collection of information media at Batik Sari Kenongo includes two methods, namely data collection methods and data collection methods. system development method. The result of this research with the existence of an e-catalog information system at Batik Sari Kenongo is that it is easy and fast for visitors to get information on Batik Sari Kenongo and with the implementation of the e-catalog, it is expected to be able to attract visitors to come to Batik Sari Kenongo. The conclusion of this study is that it is easy and fast for visitors to get information on Batik Sari Kenongo. With the implementation of the e-catalog, it is hoped that it will attract visitors to come to Batik Sari Kenongo.